KRITERIA PEMILIHAN JODOH WANITA MELAYU DI KECAMATAN MANDAH KABUPATEN INDRAGIRI HILI - Siti Astiza. Z; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The Malay community in Riau, especially in Mandah District, Indragiri Hilir Regency, since the era of reform and regional autonomy has experienced rapid development with various regional development activities. This encourages higher socio-cultural contact between the community and the outside world, supported by the rapid advancement of transportation and communication facilities. This condition of openness has brought about many changes in various aspects of community life, especially in the culture of Malay marriage which begins with the determination of criteria and the procession of choosing a mate in the process of discussing potential partners. Today, Malay women have changed in the choice of mate. Malays that are identical to Islam, it turns out that the criteria of religion and descent from the heritage of the past have changed towards an assessment of economic wealth with certain occupations of interest. This research tries to find out how the criteria and procession of mate selection among Malay women and how the changes that occur and the dominant factors that cause change. This type of research is descriptive quantitative by determining a number of 70 married women respondents. The results showed that the criteria for mate selection experienced significant changes from the criteria of religion, descent, occupation, wealth and education, to the dominant economic assessment, namely ownership of wealth with occupational professions that were of interest to be Tauke/ Juragan, borjuis, entrepreneur and civil servant. The existence of women in determining a more personal mate by changing the old tradition of matchmaking, because it is supported by adequate education, the dowry of marriage turns into a large enough amount of money as a guarantee for married life.  Keywords : Match Selection, Malay Woman and Change.